Quality of life after partial lung resection with uniportal versus 3-port video-assisted thoracoscopic surgery: a prospective randomized controlled study - Sano, Yoshifumi; Okazaki, Mikio; Shigematsu, Hisayuki; Yamashita, Natsumi; Sugimoto, Ryujiro; Sakao, Nobuhiko; Mori, Yu; Yukumi, Shungo; Izutani, Hironori (Surgery today (Tokyo, Japan), 2021)
Purpose The effect of uniportal video-assisted thoracoscopic surgery (uni-VATS) versus that of conventional VATS on postoperative quality of life (QOL) is unclear. This prospective randomized controlled study compared uni-VATS and conventional 3-port VATS in terms of QOL and patient satisfaction. Methods The subjects of this study were 84 patients with pulmonary nodules or bullous formation, randomized to undergo uniportal or conventional 3-port video-assisted thoracoscopic partial lung resection. The primary endpoint was postoperative pain, assessed using a numeric rating scale on postoperative day (POD) 1. Results No differences were found in the numeric rating scale on POD 1 after uni-VATS and conventional 3-port VATS. There were also no differences in blood loss, operative time, complication rate, surgical margin, analgesic requirement, vital capacity (VC), forced expiratory volume in 1 s (FEV1), the 6-min walk test (6MWT), C-reactive protein (CRP) levels, white blood cell count (WBC), or duration of chest tube drainage and hospital stay. Differences were found in the numeric rating scale on days 2, 3, 5, and 10 and in the patient satisfaction score on PODs 5 and 10. Conclusions Uni-VATS is associated with less chest pain and better patient satisfaction in the short term but without differences in complication rates or surgical margins from the lesions. Clinical trial registry number University Hospital Medical Information Network Clinical Trial Registry (UMIN000015340 http://www.umin.ac.jp/english/ ).